Manual Reposition of Uterine Inversion with Hemorrhagic Shock in Minimal Facilities Situation - Endah Retnoningrum (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: Reporting management of acute uterine inversion with hemorrhagic shock in minimal facilities situation. Method: Case report. Results: Manual reposition in acute uterine inversion was a lifesaving treatment. The decision to do manual reposition with minimal sedation and without any tocolytic could be done in this case, due to minimal facilities situation where there is no operating theater available for ideal uterine reposition. Conclusion: Uterine inversion can be promptly recognized in the third stage of parturition. Manual manipulation aided by tocolytic with or without anesthetic agents is often successful in correcting the inversion. Shock condition that accompanied the inversion must be vigorously treated, as it would lead to serious maternal morbidity and mortality. Management of acute uterine inversion seems to be depended on the clinical situation and clinical judgment which is very important in every emergency case. [Indones J Obstet Gynecol 2012; 36-1:48-51] Keywords: hemorrhagic shock, manual reposition, minimal facilities situation, obstetric complications, uterine inversion